Battery electrolyte
By using a specific electrolyte composition in lithium-ion batteries, the resistance and swelling problems caused by silicon-based electrode materials have been solved, thereby improving the stability and cycle life of the batteries at high temperatures.
Patent Information
- Application Number
- CN202510993813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-24
- Filing Date
- 2025-07-18
- Publication Date
- 2026-02-03
AI Technical Summary
In lithium-ion batteries, the formation of lithium silicide in silicon-based electrode materials during charge-discharge cycles leads to increased cell resistance and swelling, affecting battery performance and lifespan.
An electrolyte composition comprising lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and specific additives is dissolved in ethylene carbonate and methyl ethyl carbonate solvents to form a lithium polymer structure for use in the electrode assembly of lithium-ion batteries.
It effectively reduces battery resistance and swelling, and improves battery storage stability and cycle life performance at high temperatures, especially achieving up to 500 cycles at 45°C.
Smart Images

Figure CN121460701A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to electrolytes for lithium-ion batteries. BACKGROUND
[0002] High energy density and capacity can be achieved using electrode materials such as lithium and silicon. Silicon with high specific capacity can form lithium silicide during charge and discharge cycling. Lithium silicide can irreversibly precipitate on the electrode surface, increasing cell resistance. Silicon expansion and contraction can also cause cell swelling. SUMMARY
[0003] In one aspect of the present disclosure, an electrode assembly is presented. The electrode assembly includes a positive electrode; a negative electrode; a separator positioned between the positive electrode and the negative electrode; and an electrolyte including lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and an additive dissolved in a solvent of ethylene carbonate and ethyl methyl carbonate to saturate the negative electrode, the positive electrode, and the separator, wherein the additive is (s)-n-(l-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-l-yl)methyl)pyrrolidin-l-yl)-3,3-dimethyl-l- oxobutan-2-yl)-3-methyl-2-(2-oxo-l,3-diazaspiro[4.5]decan-l-yl)butanamide. The electrolyte can include 0.7 M lithium hexafluorophosphate and 0.3 M lithium bis(fluorosulfonyl)imide. The solvent can include ethylene carbonate and ethyl methyl carbonate in a volume ratio of 25 / 75. The electrolyte can include 1 wt% fluoroethylene carbonate. The electrolyte can also include 1 wt% vinylene carbonate. In some configurations, the electrolyte can include 0.3 wt% additive. The multifunctional additive can include a sulfonic acid lactone group and a fluorinated phosphorus group within its chemical structure. The additive can form a lithium polymer structure through ring closure. In other configurations, the combination of lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and additive can result in reduced resistance and reduced swelling compared to a battery cell without the combination. The positive electrode and the negative electrode can have increased swelling inhibition at 60 °C compared to a battery cell without the electrolyte. In other configurations, the positive electrode and the negative electrode can exhibit improved cycle life performance up to 500 cycles at 45 °C compared to a battery cell without the electrolyte.
[0004] In another aspect of the disclosure, a method of making a battery cell is presented. The method includes positioning a separator between a negative electrode and a positive electrode; dissolving 0.7 M lithium hexafluorophosphate, 0.3 M lithium bis(fluorosulfonyl)imide, 1 wt% fluoroethylene carbonate, 1 wt% vinylene carbonate, and 0.3 wt% of a multifunctional additive in a solvent mixture of ethylene carbonate and ethyl methyl carbonate in a 25 / 75 volume ratio to form an electrolyte, wherein the multifunctional additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidin-1-yl)-3,3-dimethyl-1- oxobutan-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]dec-1-yl)butanamide; and saturating the negative electrode, the positive electrode, and the separator with the electrolyte. The multifunctional additive can include a sulfonic acid lactone group and a fluorinated phosphorus group within its chemical structure. The multifunctional additive can form a lithium polymer structure through ring closure.
[0005] In yet another aspect of the disclosure, an electrolyte for a battery cell is presented. The electrolyte includes 0.7 M lithium hexafluorophosphate, 0.3 M lithium bis(fluorosulfonyl)imide, 1 wt% fluoroethylene carbonate, 1 wt% vinylene carbonate, 0.3 wt% of a multifunctional additive, and a solvent mixture of ethylene carbonate and ethyl methyl carbonate in a 25 / 75 volume ratio, wherein the multifunctional additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidin-1-yl)-3,3-dimethyl-1- oxobutan-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]dec-1-yl)butanamide. The multifunctional additive can include a sulfonic acid lactone group and a fluorinated phosphorus group within its chemical structure. The multifunctional additive can form a lithium polymer structure through ring closure. In some configurations, the lithium bis(fluorosulfonyl)imide, the fluoroethylene carbonate, the vinylene carbonate, and the multifunctional additive can result in a decrease in resistance and a decrease in swelling of the battery cell compared to a battery cell without the electrolyte. The battery cell with the electrolyte can have increased swelling suppression at 60 °C compared to a battery cell without the electrolyte. The battery cell with the electrolyte can have improved cycle life performance up to 500 cycles at 45 °C compared to a battery cell without the electrolyte. BRIEF DESCRIPTION OF DRAWINGS
[0006] Figure 1 is a schematic of an additive according to one or more aspects of the disclosure;
[0007] Figure 2 is a schematic of an additive according to one or more aspects of the disclosure;
[0008] Figure 3 is a plot of differential potential versus differential voltage for a battery having an electrolyte incorporating an additive in Figure 2
[0009] Figure 4 is a linear sweep voltammetry plot for a battery having an electrolyte incorporating an additive in Figure 2
[0010] Figure 5 is a table of electrolyte compositions according to one or more aspects of the present disclosure and properties thereof;
[0011] Figure 6 is a table of electrolyte compositions according to one or more aspects of the present disclosure and properties thereof;
[0012] Figure 7 is a plot of retention percentage for a battery incorporating an electrolyte according to one or more aspects of the present disclosure;
[0013] Figure 8 is a plot of direct current internal resistance for a battery incorporating an electrolyte according to one or more aspects of the present disclosure;
[0014] Figure 9 is a plot of percentage swell for a battery incorporating an electrolyte according to one or more aspects of the present disclosure; and
[0015] Figure 10 is a schematic of a battery having an electrolyte according to one or more aspects of the present disclosure. DETAILED DESCRIPTION
[0016] Detailed embodiments are disclosed herein as required by the prior art; however, it is to be understood that the disclosed embodiments are merely representative of the embodiments of the application and can be embodied in various and alternative forms. The Figures are not necessarily drawn to scale; some features can be exaggerated or minimized for the purpose of clarity. Therefore, specific structural and functional details disclosed herein are not to be interpreted as limiting, but merely as a representative basis for teaching one skilled in the art to employ the embodiments of the application in variously different embodiments.
[0017] Unless explicitly stated otherwise, all numerical values and ranges involving quantities, measurements, percentages, weights, and like numerical references within this document should be interpreted as being preceded by the term "about." This applies even if the term "about" is not explicitly used. It is intended that all values and ranges encompass variations that can arise due to standard measurements, manufacturing processes, material properties, and expected functionality of aspects of the present disclosure. For example, when a liquid electrolyte is described as having "5 weight percent of a component," it should be understood as "about 5 weight percent of a component." Further, when a numerical value is presented as a range, such as "100 to 200 units," the range should be interpreted as actually meaning "about 100 to about 200 units." Such variations are implicitly incorporated into the scope of the present disclosure.
[0018] The present disclosure relates to an electrolyte composition for lithium (Li) ion batteries designed to improve performance and longevity under various conditions. A particular multifunctional additive (MFA), ((s)-n-(l-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-l-yl)methyl)pyrrolidin-l-yl)-3,3-dimethyl-l-oxobutan-2-yl)-3-methyl-2-(2-oxo-l,3-diazaspiro[4.5]decan-l-yl)butanamide), is identified for inclusion in the electrolyte composition. The MFA incorporates both a sulfonate ester group and a fluorinated phosphorus group and has the potential to form a Li polymer structure through ring closure. The electrolyte presented includes a combination of 0.7 moles (M) of lithium hexafluorophosphate (LiPF6) as a primary salt; 0.3 M of lithium bis(fluorosulfonyl)imide (LiFSI) as a secondary salt; a solvent mixture of ethylene carbonate / ethyl methyl carbonate (EC / EMC) at 25 / 75 volume percent; and an additive that includes 1 weight percent of fluoroethylene carbonate (FEC), 1 weight percent of vinyl carbonate (VC), and 0.3 weight percent of the MFA. The formulation exhibits swelling inhibition under high temperature storage conditions (60 °C) and maintains cycle life performance up to 500 cycles at high temperature (45 °C). LiPF6 ) as a primary salt; 0.3 M of lithium bis(fluorosulfonyl)imide (LiFSI) as a secondary salt; a solvent mixture of ethylene carbonate / ethyl methyl carbonate (EC / EMC) at 25 / 75 volume percent; and an additive that includes 1 weight percent of fluoroethylene carbonate (FEC), 1 weight percent of vinyl carbonate (VC), and 0.3 weight percent of the MFA. The formulation exhibits swelling inhibition under high temperature storage conditions (60 °C) and maintains cycle life performance up to 500 cycles at high temperature (45 °C).
[0019] Figure 1 is a schematic of the chemical structure of the additive 1,3-propanediol cyclic sulfate (PA355). The structure has a six-membered ring forming the core of the molecule. At the top of the ring is a CH2 group, represented by a simple line forming a point. This is connected to two oxygen atoms, one on each side, with the "O" symbol. At the bottom of the ring structure is a sulfur atom, with "S." This sulfur atom is connected to the rest of the ring by four lines, indicating that it forms a sulfate group with double bonds to the two oxygen atoms. The cyclic sulfate imparts to the molecule its properties as a sulfate-based additive, which can be beneficial for use in battery electrolytes or other chemical processes.
[0020] Figure 2is a schematic representation of the chemical structure of the additive (S)-N-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidin-1-yl)-3,3-dimethyl-1- oxobutan-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decan-1-yl)butanamide (PA800). The structure is represented as an ionic compound with two distinct parts. On the left is the negatively charged complex anion in square brackets. This anion contains two phosphorus atoms, each bonded to two fluorine atoms and two oxygen atoms. It also includes a sulfur atom bonded to two oxygen atoms, and two Li ions associated with the oxygen atoms. On the right is the cation, specifically an ethylammonium ion. This cation has a positively charged central nitrogen atom, three ethyl (CH2CH3) groups attached to the nitrogen, and one hydrogen atom also attached to the nitrogen. This ionic structure imparts properties to PA800, making it useful as an electrolyte additive in battery applications, where its complex chemical composition can enhance performance or stability.
[0021] Figure 3 is a plot of the differential capacity (dQ / dV) versus voltage in electron volts per volt (Ewb / V) for batteries with and without Figure 2 is a plot of the differential capacity (dQ / dV) versus voltage in electron volts per volt (Ewb / V) for batteries with and without Figure 3 shows the high reducing and solid electrolyte membrane forming properties of PA800. The x-axis represents voltage ranging from 1.8 to 3.2 volts (V), while the y-axis shows differential capacity ranging from 0 to 300 microampere hours per volt (μAh / V). The plot compares a base electrolyte without additives, labeled “No Additive,” to the same base electrolyte with 1 weight percent of the PA800 additive. The base electrolyte composition is 1 M EC / EMC in a 3 / 7 volume by volume (v / v) ratio. The battery electrode is nickel cobalt manganese (NCM) 811 paired with graphite, NCM being a cathode material with a ratio of 80% nickel, 10% cobalt, and 10% manganese. The dashed box highlights the region between approximately 2.2 volts and 2.4 volts, labeled “PA800 Reduction,” where the PA800 additive undergoes reduction, contributing to the formation of a solid-electrolyte interface (SEI) layer. The curves show a clear difference in behavior, with the “No Additive” curve showing a peak around 3V followed by a decline, while the PA800 curve shows a more gradual increase with multiple smaller peaks between 2.8V and 3.2V. This comparison shows that the addition of PA800 changes the electrochemical behavior of the battery, potentially improving the formation of a stable SEI layer and increasing the overall performance of the battery.
[0022] Figure 4 is a plot of the differential capacity (dQ / dV) versus voltage in electron volts per volt (Ewb / V) for batteries with and without Figure 2Linear sweep voltammetry (LSV) plot of the high oxidative stability of battery electrolytes with PA800 additive shown in FIG. 8. The x-axis represents the potential (V) ranging from 3 V to 7 V, while the y-axis shows the current in milliampere (mA) ranging from 0 to 1.60. The plot compares two electrolyte compositions, the base electrolyte without additive labeled “No Additive” and the same base electrolyte with 1 wt% of PA800 additive labeled “PA800 1%”. The working electrode is platinum (Pt) vs. Li / Li + at 1 millivolt / second (mV / sec) and a scan range of 3 V to 7 V. The inset provides additional data showing the current density at 0.1 mA / cm 2 The threshold is reached at 5.42 V for the “No Additive” electrolyte and at 5.66 V for the PA800 1 wt% electrolyte at a current density of 0.1 mA / cm
[0023] Figure 5 is a table of electrolyte compositions showing their various formulations and their impact on battery performance. The reference sample (Ref. 1) includes 1.0 M LiPF6, 25% EC, 75% EMC, 1.0 wt% FEC, and 1.0 wt% VC. The first set of compositions (Nos. 2-5) explores the impact of salt-type additives and PA800. These compositions maintain the base electrolyte while including different additives: 1.0 wt% lithium difluorophosphate (LiPO2F2 or PA77) in the No. 2 composition; 0.3 wt% PA800 in the No. 3 composition; 0.5 wt% PA800 in the No. 4 composition; and 0.3 wt% PA355 in the No. 5 composition. This series aims to evaluate the impact of these additives on electrolyte performance. The next set of compositions (Nos. 6-7) investigates the impact of 1,3-propane sultone (PS). These compositions incorporate 0.5 wt% and 1.0 wt% of PS, respectively, while keeping other components constant. Experiments Nos. 8-10 focus on the impact of PA355 with 0.3 wt%, 0.5 wt%, and 1.0 wt%, respectively. Experiment No. 11 introduces a dual salt system. This composition includes 0.7 M LiPF6 and 0.3 M LiFSI while maintaining other components. The final set of compositions (Nos. 12-14) builds on this dual salt system, combining 0.7 M LiPF6 and 0.3 M LiFSI with 0.3 wt% and 0.5 wt% of PA800, respectively, while No. 14 adds 0.5 wt% of PS to the dual salt base.
[0024] Design of Experiments (DOE) specified certain compositions that showed particularly promising results. Specifically, having 0.5 wt% PS (No. 6), 0.5 wt% PA355 (No. 9), and 0.3 wt% PA800 (No. 3) exhibited swelling inhibition and reduced direct current internal resistance (DC-IR) under 60 °C storage test conditions. These compositions also exhibited acceptable cycle life performance at 45 °C. Based on these findings, additional experiments (Nos. 11-14) were conducted to explore the possibility of combining the dual salt system with the most effective additives.
[0025] Figure 6 is a table of electrolyte compositions and their corresponding properties. The reference composition (No. 1 Ref.) includes 1.0 M LiPF6 as the salt, with a solvent mixture of 25 vol% EC and 75 vol% EMC. The reference also includes 1.0 wt% FEC and 1.0 wt% VC as additives. The properties of this reference electrolyte are listed as 3.12 centipoise (cP) viscosity, 9.241 microsiemens per centimeter (μS / cm) conductivity, 1.1978 grams per cubic centimeter (g / cm3) density, 11.495 parts per million (ppm) hydrofluoric acid (HF) content, and a 4 on the American Public Health Association Hazen scale (APHA) color rating. Subsequent rows explore the effects of modifying this base composition. No. 11 composition includes a dual salt system, replacing a portion of the LiPF6 with LiFSI. This composition uses 0.7 M LiPF6 and 0.3 M LiFSI, maintaining the same solvent and additive proportions as the reference. This change results in a decrease in viscosity to 3.00 cP, a slight increase in conductivity to 9.526 μS / cm, a slight decrease in density to 1.1968 g / cm3, and an increase in HF content to 31.944 ppm. The color rating also increases to 7 APHA. 3 ) density, 11.495 parts per million (ppm) hydrofluoric acid (HF) content, and a 4 on the American Public Health Association Hazen scale (APHA) color rating. Subsequent rows explore the effects of modifying this base composition. No. 11 composition includes a dual salt system, replacing a portion of the LiPF6 with LiFSI. This composition uses 0.7 M LiPF6 and 0.3 M LiFSI, maintaining the same solvent and additive proportions as the reference. This change results in a decrease in viscosity to 3.00 cP, a slight increase in conductivity to 9.526 μS / cm, a slight decrease in density to 1.1968 g / cm3, and an increase in HF content to 31.944 ppm. The color rating also increases to 7 APHA.
[0026] Composition No. 12, which added 0.3 wt% of PA800 to the double salt composition, resulted in a slight increase in viscosity to 3.05 cP, a decrease in conductivity to 9.311 pS / cm, a small increase in density to 1.1972 g / cm3, and a significant decrease in HF content to 30.649 ppm. The color rating increased to 8 APHA. Composition No. 13 explored the effect of 0.5% PA355, which resulted in a significant decrease in viscosity to 2.43 cP, a slight decrease in conductivity to 9.233 pS / cm, a small increase in density to 1.1977 g / cm3, and a decrease in HF content to 28.132 ppm. The color rating also increased to 12 APHA. Composition No. 14 examined the effect of 0.5% PS, which resulted in similar properties to the PA355 composition, with a viscosity of 2.42 cP, a conductivity of 9.214 pS / cm, a density of 1.1979 g / cm3, and an HF content of 28.083 ppm. The color rating for this composition was the highest at 13 APHA.
[0027] Figure 7 is a plot of the capacity retention performance of various electrolyte compositions over 500 charge-discharge cycles. The plot shows the percent retention on the y-axis ranging from 75% to 100%, plotted against the cycle number on the x-axis from 0 to 500. Nickel / graphite soft pack battery cells were used as the test conditions, where they were charged at 1 charge / discharge rate (C) ampere hour (Ah) to a 4.2 V cutoff (0.02 C) and discharged at 1 C (Ah) to 2.7 V. The plot compares five different electrolyte compositions labeled as No. 1, No. 11, No. 12, No. 13, and No. 14, which correspond to the compositions specified in Figure 6 .
[0028] No. 1 reference composition had a moderate rate of capacity loss, resulting in about 85% retention after 500 cycles. No. 11 composition, which represents a double salt system, performed slightly worse than the reference, ending with about 84% retention. No. 12 composition, which includes a double salt system and PA800, had the best performance. It maintained the highest capacity retention throughout the test, reaching about 90% after 500 cycles. In contrast, No. 13 composition, which has a double salt system and PA355, had an initial rapid capacity loss of up to about 150 cycles before stabilizing, ending with about 82% retention. No. 14 composition, which incorporates a double salt system and PS, exhibited the worst performance, with the steepest initial drop and the lowest final retention of about 79%. This shows that adding PA800 to the double salt system (No. 12) increased the capacity retention over an extended cycle. In contrast, the other additives (PA355 and PS) did not improve performance compared to the reference or double salt system alone.
[0029] Figure 8is a plot of DC-IR of electrolyte compositions at 50% state of charge (SOC) over a 4 week storage period at 60 °C. The plot shows the percent change in DC-IR on the y-axis ranging from -40% to 80%, plotted against the storage period in weeks (0 to 4) on the x-axis. Test conditions included nickel / graphite soft-pack battery cells. The DC-IR check was performed at SOC 50% at varying C-rates (0.5C / 1.0C / 2.0C / 2.5C) for 10 seconds. The plot compares five different electrolyte compositions, namely No. 1, No. 11, No. 12, No. 13, and No. 14. All compositions started with 0% DC-IR change at week 0, but they exhibited different behavior over the 4 week storage period. The No. 1 reference composition showed relatively stable performance with minor fluctuations, ending with a slightly negative DC-IR change after 4 weeks. The No. 11 composition, representing a double salt system, exhibited the least stable behavior, with large positive spikes in DC-IR at weeks 2 and 4, indicating an increase in internal resistance.
[0030] The No. 12 composition, which includes a double salt system and PA800, showed more stable performance compared to the No. 11 composition, with less fluctuation and a modest increase in DC-IR by week 4. The No. 13 and No. 14 compositions, featuring double salt systems with PA355 and PS, respectively, showed similar trends to each other. They both exhibited an initial decrease in DC-IR followed by an increase, with No. 13 ending with slightly higher DC-IR than No. 14 after 4 weeks. The No. 12 composition appears to provide a good balance, showing less fluctuation in DC-IR compared to the other double salt compositions. This suggests that adding PA800 to a double salt system can help stabilize the internal resistance of the battery during prolonged high-temperature storage.
[0031] Figure 9is a graph of the swell ratio of nickel / graphite soft-pack battery cells having various electrolyte compositions at 60 °C over a 4 week storage period. The graph shows the percent swell ratio on the y-axis ranging from 0% to 90%, plotted against the storage period in weeks (0 to 4) on the x-axis. The graph compares five different electrolyte compositions, labeled as 1, 11, 12, 13, and 14. All compositions start at 0% swell at week 0, but they exhibit different swell behavior over the 4 week storage period. The 1 reference composition shows the highest swell ratio, reaching about 78% at the end of week 4. This indicates that the reference electrolyte provides the least protection against cell swell under high temperature storage conditions. The 11 composition, which represents a bisalt system, exhibits improved resistance to swell compared to the reference, with a final swell ratio of about 62% after 4 weeks. This indicates that the bisalt system alone provides some benefit in reducing cell swell. The 12 composition, which includes both a bisalt system and PA800, shows the best performance in terms of resistance to swell. It shows the lowest swell ratio throughout the test period, reaching only about 45% swell by week 4. This improvement over both the reference and the bisalt system alone indicates that the addition of PA800 plays a role in mitigating cell swell under high temperature conditions. The 13 and 14 compositions, which carry a bisalt system with PA355 and PS, respectively, show intermediate performance. They both exhibit lower swell ratios than the reference and the bisalt system alone, but exhibit higher swell ratios than the PA800 composition. The 13 ends at about 53% swell, while the 14 shows slightly better performance with a final swell ratio of about 50%.
[0032] Figure 10A battery cell 10 is shown having a positive electrode 12, a negative electrode 14, and a separator 16 positioned between the positive electrode 12 and the negative electrode 14. The positive electrode 12 includes a positive active material 18 forming a layer of the positive electrode 12. The battery cell 10 includes a liquid electrolyte 20. The liquid electrolyte 20 permeates the surface of the positive active material layer and includes 0.7 M of LiPF6, 0.3 M of LiFSI, 1 wt% of FEC, 1 wt% of VC, and 0.3 wt% of MFA dissolved in a solvent of EC and EMC in a volume ratio of 25 / 75. This particular composition of the liquid electrolyte 20 is configured to suppress electrochemical oxidation of the positive active material layer 18 during electrochemical cycling. The MFA in the liquid electrolyte 20 is (s)-n-(l-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-l-yl)methyl)pyrrolidin-l-yl)-3,3-dimethyl-l- oxobutan-2-yl)-3-methyl-2-(2-oxo-l,3-diazaspiro[4.5]decan-l-yl)butanamide. The additive includes a sulfonate lactone group and a fluorinated phosphorus group within its chemical structure and is capable of forming a lithium polymer structure through ring closure. The liquid electrolyte 20 saturates the positive electrode 12, the negative electrode 14, and the separator 16 such that the combination of LiFSI, FEC, VC, and MFA results in reduced resistance and reduced swelling compared to other aspects of a battery cell that are otherwise identical except for the absence of this combination. Additionally, the battery cell 10 having this electrolyte composition has increased swelling suppression at 60 °C and improved cycle life performance up to 500 cycles at 45 °C compared to other aspects of a battery cell that are otherwise identical except for the absence of this electrolyte.
[0033] In another embodiment, the liquid electrolyte 20 includes the same composition as described above that saturates the positive electrode 12 and the negative electrode 14. The MFA can interact with the other components to form a stable interface on the electrode surface, thereby reducing impedance and improving cycle life. The solvent mixture of EC and EMC in a volume ratio of 25 / 75 provides a balance between high ionic conductivity and stability, thereby improving the performance and cycle life of the battery cell 10. The positive active material layer 18 can be composed of a suitable Li-containing compound that provides high capacity and thermal stability, thereby contributing to the overall performance and stability of the battery cell 10. The battery cell 10 is configured to retain its capacity over long periods of time and has improved performance characteristics due to the electrolyte composition, including the MFA that forms a lithium polymer structure through ring closure.
[0034] While the foregoing describes representative embodiments, these embodiments are not intended to describe all possible forms of the application. The words used in the specification are words of description rather than limitation, and it is understood that various changes can be made without departing from the scope of the claimed subject matter. Additionally, features of various implementations can be combined to form further implementations that are not explicitly described or shown.
[0035] According to the present application, there is provided an electrode assembly having: a positive electrode; a negative electrode; a separator positioned between the positive electrode and the negative electrode; and an electrolyte including lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and an additive dissolved in a solvent of ethylene carbonate and ethyl methyl carbonate, thereby saturating the negative electrode, the positive electrode, and the separator, wherein the additive is (s)-n-(l-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-l-yl)methyl)pyrrolidin-l-yl)-3,3-dimethyl-l- oxobutan-2-yl)-3-methyl-2-(2-oxo-l,3-diazaspiro[4.5]decan-l-yl)butanamide.
[0036] According to embodiments, the electrolyte includes 0.7 M lithium hexafluorophosphate and 0.3 M lithium bis(fluorosulfonyl)imide.
[0037] According to embodiments, the solvent includes ethylene carbonate and ethyl methyl carbonate in a volume ratio of 25 / 75.
[0038] According to embodiments, the electrolyte includes 1 wt% fluoroethylene carbonate.
[0039] According to embodiments, the electrolyte includes 1 wt% vinylene carbonate.
[0040] According to embodiments, the electrolyte includes 0.3 wt% of the additive.
[0041] According to embodiments, the additive includes a sulfonol group and a fluorinated phosphorus group within its chemical structure.
[0042] According to embodiments, the additive forms a lithium polymer structure through ring closure.
[0043] According to embodiments, the combination of lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and the additive results in reduced resistance and reduced swelling compared to other aspects of a battery cell that are otherwise identical except for the combination.
[0044] According to embodiments, the positive electrode and the negative electrode have increased swelling inhibition at 60 °C storage compared to other aspects of a battery cell that are otherwise identical except for the electrolyte.
[0045] According to an embodiment, compared to a battery cell that is otherwise identical without the electrolyte, the positive electrode and the negative electrode exhibit improved cycle life performance of up to 500 cycles at 45°C.
[0046] According to the present invention, a method for manufacturing a battery cell includes: positioning a separator between a negative electrode and a positive electrode; dissolving 0.7 M lithium hexafluorophosphate, 0.3 M lithium bis(fluorosulfonyl)imide, 1 wt% fluoroethylene carbonate, 1 wt% vinylene carbonate, and 0.3 wt% a multifunctional additive in a solvent mixture of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 25 / 75 to form an electrolyte, wherein the multifunctional additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidine-1-yl)-3,3-dimethyl-1-oxobut-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decane-1-yl)butanamide; and saturating the negative electrode, the positive electrode, and the separator with the electrolyte.
[0047] In one aspect of the invention, the multifunctional additive comprises sulfonyl lactone groups and phosphorus fluoride groups within its chemical structure.
[0048] In one aspect of the invention, the multifunctional additive forms a lithium polymer structure through ring closure.
[0049] According to the present invention, an electrolyte for a battery cell is provided, comprising: 0.7 M lithium hexafluorophosphate; 0.3 M lithium bis(fluorosulfonyl)imide; 1 wt% fluoroethylene carbonate; 1 wt% vinylene carbonate; 0.3 wt% a multifunctional additive, wherein the multifunctional additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidine-1-yl)-3,3-dimethyl-1-oxobut-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decane-1-yl)butanamide; and a solvent mixture of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 25 / 75.
[0050] According to an embodiment, the multifunctional additive contains sulfonyl lactone groups and phosphorus fluoride groups within its chemical structure.
[0051] According to an embodiment, the multifunctional additive is configured to form a lithium polymer structure through ring closure.
[0052] According to the embodiments, compared with battery cells that are otherwise identical without the electrolyte, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and multifunctional additives result in reduced resistance and swelling of the battery cell.
[0053] According to an embodiment, compared to a battery cell that is otherwise identical without the electrolyte, a battery cell having the electrolyte exhibits increased swelling suppression when stored at 60°C.
[0054] According to an embodiment, compared to a battery cell that is otherwise identical without the electrolyte, a battery cell having the electrolyte exhibits improved cycle life performance of up to 500 cycles at 45°C.
Claims
1. An electrode assembly comprising: Positive electrode; negative electrode; A partition, wherein the partition is positioned between the positive electrode and the negative electrode; as well as The electrolyte comprises lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, vinylene carbonate, and additives, which are dissolved in solvents of ethylene carbonate and methyl ethyl carbonate to saturate the negative electrode, the positive electrode, and the separator, wherein the additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidine-1-yl)-3,3-dimethyl-1-oxobut-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decane-1-yl)butyramide.
2. The electrode assembly of claim 1, wherein the electrolyte comprises 0.7M lithium hexafluorophosphate and 0.3M lithium bis(fluorosulfonyl)imide.
3. The electrode assembly of claim 1, wherein the solvent comprises ethylene carbonate and ethyl methyl carbonate in a volume ratio of 25 / 75.
4. The electrode assembly of claim 1, wherein the electrolyte comprises 1% by weight of ethylene fluorocarbonate.
5. The electrode assembly of claim 1, wherein the electrolyte comprises 1% by weight of vinylene carbonate.
6. The electrode assembly of claim 1, wherein the electrolyte comprises 0.3% by weight of an additive.
7. The electrode assembly of claim 1, wherein the additive comprises sulfonyl lactone groups and phosphorus fluoride groups within its chemical structure.
8. The electrode assembly of claim 1, wherein the additive forms a lithium polymer structure through a closed-loop structure.
9. The electrode assembly of claim 1, wherein the combination of the lithium bis(fluorosulfonyl)imide, the fluoroethylene carbonate, the vinylene carbonate, and the additive results in reduced resistance and reduced swelling compared to a battery cell with the same other aspects without the combination.
10. The electrode assembly of claim 1, wherein the positive electrode and the negative electrode have increased swelling suppression when stored at 60°C compared to a battery cell that is otherwise identical without the electrolyte.
11. The electrode assembly of claim 1, wherein the positive electrode and the negative electrode exhibit improved cycle life performance of up to 500 cycles at 45°C compared to a battery cell that is otherwise identical without the electrolyte.
12. A method for manufacturing a battery cell, comprising: Position the partition between the negative electrode and the positive electrode; 0.7 M lithium hexafluorophosphate, 0.3 M lithium bis(fluorosulfonyl)imide, 1 wt% fluoroethylene carbonate, 1 wt% vinylene carbonate, and 0.3 wt% a multifunctional additive were dissolved in a solvent mixture of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 25 / 75 to form an electrolyte, wherein the multifunctional additive was (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidine-1-yl)-3,3-dimethyl-1-oxobut-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decane-1-yl)butanamide; and The negative electrode, the positive electrode, and the separator are saturated with the electrolyte.
13. The method of claim 12, wherein the multifunctional additive comprises sulfonyl lactone groups and phosphorus fluoride groups within its chemical structure.
14. The method of claim 12, wherein the multifunctional additive forms a lithium polymer structure through ring closure.
15. An electrolyte for use in a battery cell, comprising: 0.7M lithium hexafluorophosphate; 0.3M lithium bis(fluorosulfonyl)imide; 1% by weight of fluoroethylene carbonate; 1% by weight of vinylene carbonate; 0.3% by weight of a multifunctional additive, wherein the multifunctional additive is (s)-n-(1-(2-((4-(3-(trifluoromethyl)phenyl)piperazin-1-yl)methyl)pyrrolidine-1-yl)-3,3-dimethyl-1-oxobut-2-yl)-3-methyl-2-(2-oxo-1,3-diazaspiro[4.5]decane-1-yl)butyramide; and A solvent mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 25 / 75.